2013
DOI: 10.1051/0004-6361/201220961
|View full text |Cite
|
Sign up to set email alerts
|

A PCA approach to stellar effective temperatures

Abstract: Context. The derivation of the effective temperature of a star is a critical first step in a detailed spectroscopic analysis. Spectroscopic methods suffer from systematic errors related to model simplifications. Photometric methods may be more robust, but are exposed to the distortions caused by interstellar reddening. Direct methods are difficult to apply, since fundamental data of high accuracy are hard to obtain. Aims. We explore a new approach in which the spectrum is used to characterize a star's effectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
5
16
2
1
Order By: Relevance
“…Torres et al (2006) quote a K0V spectral type, v sin i = 14.6 km s −1 and W Li ≃ 300 mÅ. Muñoz Bermejo et al (2013), from the analysis of our ELODIE spectrum, found T eff = 5221 K. Our determinations (K0V, T eff = 5207 K, v sin i = 14.3 km s −1 , W Li = 277±25 mÅ) are in excellent agreement with the aforementioned values from the literature. A visual companion at 5.…”
Section: Appendix A: the Datasupporting
confidence: 90%
See 3 more Smart Citations
“…Torres et al (2006) quote a K0V spectral type, v sin i = 14.6 km s −1 and W Li ≃ 300 mÅ. Muñoz Bermejo et al (2013), from the analysis of our ELODIE spectrum, found T eff = 5221 K. Our determinations (K0V, T eff = 5207 K, v sin i = 14.3 km s −1 , W Li = 277±25 mÅ) are in excellent agreement with the aforementioned values from the literature. A visual companion at 5.…”
Section: Appendix A: the Datasupporting
confidence: 90%
“…#21 RasTyc 2036+3456 (=TYC 2694-1627-1). A temperature about 160 K cooler than our value was found by Muñoz Bermejo et al (2013) from the analysis of our ELODIE spectrum. The Hα line is filled in by core emission.…”
Section: # Namecontrasting
confidence: 73%
See 2 more Smart Citations
“…3 shows, this concerns relatively small corrections of the continuum level that never exceed a few percent. As mentioned earlier by Muñoz Bermejo et al (2013), this procedure may be debatable, but we found it satisfactory, and it was consistently applied to all the spectra we used.…”
Section: Training Databasementioning
confidence: 56%